The Influence of Coordination Mechanisms on the Procurement Performance Indicators of Supply Chains Participants - Abramova, E.R.; Protsenko, I.O.; Terenina, I.V. (International Journal of Supply Chain Management, 2020)
Abstract—The proposed paper is an analysis of the impact of coordination mechanisms on the procurement performance indicators of participants in supply chains. Particular attention is paid to the study of mechanisms for joint planning, harmonization of guidance documentation in the field of process logistics management, coordination of operational procurement procedures, joint use of material, labour and information resources of partner enterprises in conjunction with the dynamics of stock status parameters, procurement volumes, percentage of completed orders, compliance with obligations for deliveries, etc. The dependence of logistic indicators on the level of use of joint activity instruments by companies in their relations with suppliers is shown; conclusions are drawn about the influence of coordination mechanisms on increasing the competitiveness of participants in integrated supply chains. When carrying out this study, methods of comparative and system analysis, expert evaluations, questionnaires, comparisons by analogy, and statistical analysis were used. The methodological basis of the study was the work of domestic and foreign scientists and practitioners in the field of logistic coordination, procurement management, and supply chain management.